2008
DOI: 10.1038/sj.bjc.6604761
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking, body mass index, hypertension, and kidney cancer risk in central and eastern Europe

Abstract: In a case -control study of kidney cancer in four central European countries, with 1097 incident cases and 1476 controls, we found an increased risk for self-reported hypertension and for obesity. Additional unknown risk factors are likely to be responsible for the high rates of kidney cancer in this region. British Journal of Cancer (2008Cancer ( ) 99, 1912Cancer ( -1915 (Murai and Oya, 2004). Smoking is an established risk factor, although the increase in risk is moderate (IARC, 2004). Other possible risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 16 publications
1
31
1
2
Order By: Relevance
“…Obesity is a risk factor with linear dependence, with an increase in BMI raising the risk of kidney cancer [1,3]. The risk ranges from 1.1 to 4.6 [3,23,[33][34][35]. In presented study, obesity, but not being overweight, showed to be risk factor for kidney cancer.…”
Section: Discussionmentioning
confidence: 78%
“…Obesity is a risk factor with linear dependence, with an increase in BMI raising the risk of kidney cancer [1,3]. The risk ranges from 1.1 to 4.6 [3,23,[33][34][35]. In presented study, obesity, but not being overweight, showed to be risk factor for kidney cancer.…”
Section: Discussionmentioning
confidence: 78%
“…En el fumador activo se observa un aumento progresivo del riesgo con acumulación de dosis (paquete-años) 13 , es posible que en el fumador pasivo ocurra del mismo modo. La paciente del caso presentó dos carcinomas distintos de mama y riñón; ambos tienen relación documentada con el tabaco.…”
Section: Discussionunclassified
“…However, this fact does not reflect the situation in women as smoking prevalence and also mortality from other oncologic disease related to smoking in women in the majority of European countries including both SR and CR rises in the last years [14,18,19]. Smoking is an established risk factor for kidney cancer, although the increase in risk is weak [20,21]. Hunt et al [22] reported the increased risk for ever smokers compared to never smokers and also a strong dose-dependent increase with increasing tobacco consumption.…”
Section: Graph 4 Trends Of the Age-adjusted (To The World Standard Pmentioning
confidence: 99%